2021
DOI: 10.3389/fpsyg.2020.613659
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Big Five Personality and Social Well-Being of Chinese Residents: The Mediating Effect of Social Support

Abstract: Previous studies have noted that personality traits are important predictors of well-being, but how big five personality influences social well-being is still unknown. This study aims to examine the link between big five personality and five dimensions of social well-being in the Chinese cultural context and whether social support can play the mediating effect in the process. This study included 1,658 participants from different communities in China, and regression analyses were conducted. Results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
(86 reference statements)
2
25
2
1
Order By: Relevance
“…Similarly, agreeableness can be predicted by GHQ-12A, GHQ-12B, and GHQ-12C. Although there is little evidence suggesting if agreeableness is related to social dysfunction & anhedonia, Yu et al [100] discovered that Agreeableness was positively linked to all ve aspects of social well-being. Kaplan et al [101] found that social anxiety had a weak but signi cant relationship with agreeableness.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, agreeableness can be predicted by GHQ-12A, GHQ-12B, and GHQ-12C. Although there is little evidence suggesting if agreeableness is related to social dysfunction & anhedonia, Yu et al [100] discovered that Agreeableness was positively linked to all ve aspects of social well-being. Kaplan et al [101] found that social anxiety had a weak but signi cant relationship with agreeableness.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 3 months after the end of the lockdown, also the agreeableness trait emerged as a protective factor against worry levels. Agreeable people tend to have more resources for social support (Barańczuk, 2019;Yu et al, 2020) which contribute to reducing worry by means of positive social interactions and shared meaning-making regarding distressing events (Zysberg and Zisberg, 2020;Al-Omiri et al, 2021). The fact that such a protective factor emerged in the third phase specifically may be related to the renovated opportunities for social aggregation after the limitations imposed by the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…also claimed that personality significantly affects teacher effectiveness and burnout. Moreover, the recent study by Yu et al (2021) revealed that personality affects social support and social well-being. Chis (2022) also claimed that personality is related to parenting and marital satisfaction.…”
Section: Personality and Affective Commitmentmentioning
confidence: 99%